HABITAT DAN PERILAKU ELANG JAWA (Nisaetus bartelsi ) DI SPTN 1 TEGALDLIMO TAMAN NASIONAL ALAS PURWO, JAWA TIMUR - Sitorus, Desy Natalia; Hernowo, Jarwadi Budi (Department of Forest Resources Conservation and Ecotourism - IPB University, 2016)
Javan Hawk-eagle (Nisaetus bartelsi) considered as endangered species by IUCN redlist 2015 and protected species by Government Regulation No.7/1999. Alas Purwo National Park (APNP) is a conservation area and its one of the natural habitat of Javan Hawk-eagle distribution (endemic species of java). The study was aimed to analysis its habitat and the behavior. Purposive sampling was used on focused observation area base on direct contex with the bird. The habitat analysis was approach with vagetation analysis dan habitat used method. Focal animal sampling used as approach describe to know the daily activities. The result showed that the bird used of natural lowland forest as main habitat and the bird distibute as equal (focused) at natural lowland forest. Characteristic of sheltering site of the bird using tree in A strata and B strata, which have horizontal and strong enough branch. The javan hawk-eagle choising at emergent tree for the nesting site, with characteristic of emergent tree, with crown not so dense of the leaf and the position of the tree close to hunting area. Characteristic of hunting areas of the bird is natural lowland forest with diverse and abundant of preys. The bird like preys on mammals such as giant squirrel and bird such as red jungle fowl. The behavior was most often observed was resting in natural lowland forest with five times encounter (58,06%). But the bird also done activities of preening and observing surrounding to focus on seaching food. Hunting activity was observed used perch hunting in natural low land forest in APNP. Keywords: APNP, habitat, javan hawk-eagle